Navigating technological innovation and rising costs: Assessing economic performance in Chinese manufacturing. - Songling Wu; Yanqi Si; Xiaoxiang Wang (PLoS ONE)
Economic performance is an important indicator of the efficiency and quality of a company's production, which is closely related to the profitability of the company and is crucial for the development of the manufacturing industry.This paper aims to develop a theoretical framework for assessing economic performance within the Chinese manufacturing industry. It achieves this by incorporating inputs, outputs, and energy consumption costs into the production function. By analyzing manufacturing data from 2000 to 2021, it quantifies the impact of various factors, including labor costs and technological advancements, on economic performance. The findings highlight technological progress as the primary driver of economic growth within the Chinese manufacturing sector. Notably, there exists a U-shaped relationship between technical progress and economic performance, suggesting nuanced dynamics at play. Contrary to expectations, the rate of change in per capita wages shows no significant positive impact on economic performance. However, technical progress in the eastern and central regions exhibits a capital bias and positively influences economic performance. Similarly, a U-shaped relationship characterizes the relationship between the western region and manufacturing industry performance. These results underscore the crucial role of technological innovation in sustaining economic performance amid challenges such as rising labor and environmental costs. Emphasizing the reliance on scientific and technological progress emerges as imperative for enhancing the industry's economic resilience and growth.